2023
DOI: 10.3389/fgene.2023.997383
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq data science: From raw data to effective interpretation

Abstract: RNA sequencing (RNA-seq) has become an exemplary technology in modern biology and clinical science. Its immense popularity is due in large part to the continuous efforts of the bioinformatics community to develop accurate and scalable computational tools to analyze the enormous amounts of transcriptomic data that it produces. RNA-seq analysis enables genes and their corresponding transcripts to be probed for a variety of purposes, such as detecting novel exons or whole transcripts, assessing expression of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 129 publications
0
18
0
1
Order By: Relevance
“…Bulk RNA-seq has been widely applied for capturing aggregate snapshots of gene expression within tissues [1,2]. The advent of single-cell level technologies has brought in a new era, revealing cellular heterogeneity at a higher resolution that was not observable by bulk approaches [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk RNA-seq has been widely applied for capturing aggregate snapshots of gene expression within tissues [1,2]. The advent of single-cell level technologies has brought in a new era, revealing cellular heterogeneity at a higher resolution that was not observable by bulk approaches [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown differences in both gene expression and cell composition between singlecell, single-nucleus, and bulk RNA-seq data [4,[6][7][8][9][10]. In some cases, cell dissociation and processing in singlecell RNA-seq could introduce complete or partial cell loss in cell types that are adherent, sensitive, too large, or have low capture efficiency [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we employed omics techniques to investigate the underlying mechanism by which hA-MSCs modulate the immune system. Omics sciences are a rapidly evolving class of disciplines that utilize high-throughput technologies such as genomics, transcriptomics, proteomics, metabolomics, and computational biology to advance research and clarify mechanisms underlying complex diseases [ 37 , 38 , 39 ]. The study of transcriptome changes and the comparison of gene expression profiles involved in various pathologies have the potential to advance both therapeutics and diagnostics in health care and promote preventive medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The aspect of comparing reproducibility and the impact of the alignment process on further analysis has been the subject of a large number of publications. Recently, the challenges of aligning RNA-seq reads to a reference genome have been discussed, in particular the handling of spliced junctions—different aligners may handle these spliced junctions differently, leading to variations in results 12 . It has also been noted that RNA-seq alignment tools typically have a user-defined threshold for tolerating mismatches in the alignment, although it is also important to distinguish between sequencing errors and true variation between transcripts, as in some cases reads may contain mismatches caused either by sequencing errors or biological variation due to mutations 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the challenges of aligning RNA-seq reads to a reference genome have been discussed, in particular the handling of spliced junctions—different aligners may handle these spliced junctions differently, leading to variations in results 12 . It has also been noted that RNA-seq alignment tools typically have a user-defined threshold for tolerating mismatches in the alignment, although it is also important to distinguish between sequencing errors and true variation between transcripts, as in some cases reads may contain mismatches caused either by sequencing errors or biological variation due to mutations 12 , 13 . It has been argued that the differences depend on the specific requirements of the research project, including considerations of accuracy, run time, memory usage, output format, and specific features such as handling multi-reads or splice junctions, which may influence the choice of aligner.…”
Section: Introductionmentioning
confidence: 99%